2003
DOI: 10.1086/373936
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroups Do Not Play a Role in the Variable Phenotypic Presentation of the A3243G Mutation

Abstract: Thirty-five mitochondrial (mt) DNAs from Spain that harbor the mutation A3243G in association with either MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and strokelike episodes) syndrome or a wide array of disease phenotypes (ranging from diabetes and deafness to a mixture of chronic progressive external ophthalmoplegic symptoms and strokelike episodes) were studied by use of high-resolution restriction fragment length polymorphism analysis and control-region sequencing. A total of 34 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 36 publications
4
38
1
1
Order By: Relevance
“…46 Our data suggest a possible distortion towards haplogroup cluster HV among patients with early-onset but postlingual hearing impairment, at least compared with population controls or patients with ARHI, although of borderline statistical significance. Previous associations with longevity 31 suggest that tightly age-matched controls might be needed to judge the issue definitively.…”
Section: Mitochondrial Haplogroup Affiliations and Hearing Impairmentmentioning
confidence: 49%
“…46 Our data suggest a possible distortion towards haplogroup cluster HV among patients with early-onset but postlingual hearing impairment, at least compared with population controls or patients with ARHI, although of borderline statistical significance. Previous associations with longevity 31 suggest that tightly age-matched controls might be needed to judge the issue definitively.…”
Section: Mitochondrial Haplogroup Affiliations and Hearing Impairmentmentioning
confidence: 49%
“…14 We therefore sequenced the complete mtDNA of 27 patients, searching for susceptibility mtDNA mutations. Among this group, 22 individuals were familiar cases belonging to pedigrees with either mother-to-child transmission in more than one generation or with all-affected siblings in the sibship (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the m.7510T>C mutation arose on different mitochondrial subgroups provides further evidence for the pathogenecity of this mutation. Evolutionary studies showed that deleterious mitochondrial mutations are influenced very strongly by selection and are eliminated rapidly, so their appearance should be the result of very recent mutational events and transmitted through very few generations; thus, founder events are not likely to be found (Torroni et al 2003). The finding that all four so far described families carry the m.7510T>C mutation on different European mtDNA haplogroup backgrounds indicates that European haplogroups do not increase or reduce the risk of expressing the disease phenotype.…”
Section: Discussionmentioning
confidence: 97%